Government expenditure on human capital and growth in Namibia: A time series analysis - Christopher P. P. Shafuda; Utpal Kumar De (Journal of Economic Structures, 2020)
An attempt is made in this paper to examine the impacts of government spending on human capital on human development indicators like healthcare outcomes, education achievements and increase in national income in Namibia using time series data from 1980 to 2015. The analysis reveals a significant long-run inverse relationship of government spending on healthcare with fertility rate, infant mortality rate and under-5 mortality rate. However, no cointegration is observed between government spending on healthcare and life-expectancy or adult mortality rate. Also, the findings reveal a significant long-run positive relationship of government spending on education with literacy rate, net primary and gross tertiary enrolment rate. Whereas, no cointegration between government spending on education and gross enrolment rate at primary and secondary level is observed. The vector auto-regression analysis revealed significant impacts of expenditure on healthcare and education on the GDP growth in the long run through improved human resources. The results are thus in favour of continuation of expansionary government expenditure policy to achieve faster economic growth in Namibia. However, drastic changes should be adopted to improve basic education and primary healthcare in the country.
Keywords: E62; H11; H41; H71; H75 C13; I18; I28; 330; Fiscal policy; Human capital; Healthcare and education expenditure; Development; Co-integration; Error correction model; Namibia